Optimizing guava (Psidium guajava L.) breeding programs: The role of genotype selection in enhancing growth, yield and nutrient content (Indian Journal of Arid Horticulture, 2025)
This study examines genetic variation and its impact on key growth, yield, and quality traits in guava genotypes through analysis of variance and per se performance of cross combinations. The results indicate significant genetic effects on most traits, with the highest variations observed for days to first flowering (DTFF), days to first harvest (DTFH), number of seeds per fruit (NSPF), total phenols (TPH), and total antioxidant activity (TAA), highlighting the potential for selection based on these traits. The study also identifies traits with lower genetic variability, such as acidity (Acid) and pulp thickness (PT), suggesting their dependence on environmental or management factors. The ANOVA results revealed significant impacts of genotypes on key traits related to growth, yield, and fruit quality, with extremely high F-values (p< 0.0001) for most traits, suggesting that genotype plays a dominant role in the expression of these characteristics. Notably, the cross combinations, including G-28 × Lalit and G-15 × VL, showed strong potential for improving growth and quality parameters. G-28 × Lalit demonstrated superior growth and nutrient content, while G-15 × VL excelled in quality traits such as sugar content, total soluble solids (TSS), and antioxidant properties. Additionally, other cross combinations like VL × G-15 and G-31 × TP offered promising results for increasing biomass, yield, and fruit quality. Further multi-generational evaluations and environmental studies are essential to assess the stability and heritability of these traits under diverse conditions. The study highlights the importance of genotype selection for developing high-performing guava cultivars, emphasizing the need for further research to optimize breeding strategies for improved yield, quality, and resilience.